2019
DOI: 10.1002/pen.25103
|View full text |Cite
|
Sign up to set email alerts
|

Study of tensile properties of multiwalled carbon nanotube/polyether ether ketone polymer composites at the nanoscale

Abstract: This study demonstrates the microscale and nanoscale mechanical properties of a multiwalled carbon nanotubes/ polyether ether ketone (MWCNTs/PEEK) composite utilizing a novel in situ testing method. Nanoscale testing specimens of a composite of PEEK thin film dispersed with 6.5 wt% MWCNTs were successfully prepared using focused ion beam (FIB) and investigated by a tensile testing device accommodated inside a field emission scanning electron microscope. The average tensile strength of the nanocomposite was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Ashby plot. [79][80][81][84][85][86]89,93,94 Overall, the presence of CNTs can increase the elastic modulus E remarkably, while the increase in ultimate tensile strength r uts is still limited due to various problems. For example, the direct extrusion mixing can hardly result in a uniform distribution of CNTs among PEEK matrix, and thus the strengthening was still limited even at a high CNT fraction, as reported by Deng et al 85 When the fraction was up to 15 wt%, r uts was just increased from 93.55 to 110.90 MPa, by just 18.5%, whereas E was increased from 4.0 to 7.55 GPa, by 88.8%.…”
Section: Preparation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ashby plot. [79][80][81][84][85][86]89,93,94 Overall, the presence of CNTs can increase the elastic modulus E remarkably, while the increase in ultimate tensile strength r uts is still limited due to various problems. For example, the direct extrusion mixing can hardly result in a uniform distribution of CNTs among PEEK matrix, and thus the strengthening was still limited even at a high CNT fraction, as reported by Deng et al 85 When the fraction was up to 15 wt%, r uts was just increased from 93.55 to 110.90 MPa, by just 18.5%, whereas E was increased from 4.0 to 7.55 GPa, by 88.8%.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…For the sandwich-like CNT film/PEEK composites, r uts and E were improved from 113.2 MPa and 2.67 GPa to 118.2 and 3.73 GPa, respectively. 89 In order to find out the upper limit of CNT reinforcement, Hsu et al 94 designed an in situ tensile testing inside a scanning electron microscope (SEM) on which dog-bone specimens with dimensions of 20 mm  4 mm  $800 nm were tested. From the stress-strain curves (Figure 2(d)), it is found that these samples were much stronger than and as stiff as the macroscopic samples, with r uts ¼ 369-417 MPa and E ¼ 5.99-7.36 GPa.…”
Section: (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…PEEK adheres well to carbon fibers, 8 carbon nanotubes 9 and other fillers, 10 which can be used to further improve the mechanical and thermal properties of PEEK. PEEK and reinforced PEEK are widely used in biomedical applications as artificial scaffolds 11 or as implants without requiring any additional coatings or modifications because of their bioinert nature 12,13 .…”
Section: Introductionmentioning
confidence: 99%